Responsible design thinking: Informing future models of cross-disciplinary design education. (22nd December 2022) - Fridman, Ilya; Meron, Yaron; Roberts, Julie
This article provides a critical commentary of Design Thinking education and proposes a new model for incorporating responsibility within these teaching and learning practices. The need for this approach becomes more urgent as Design Thinking is increasingly integrated across disciplinary boundaries into business schools where it is seen as a pathway to commercial innovation that ultimately impacts society. Within this article, Responsible Design literature is reviewed to identify principles and practices that can inform Design Thinking education, bringing critical depth, as well as social and environmental impact into its broader ambit. It is argued that principles of social responsibility, environmental sustainability, ethics, critical thinking and accountability can be combined with feasibility, viability and desirability to create a new model for Responsible Design Thinking education. Based on these principles, three different conceptualizations are presented to indicate how Responsible Design Thinking may be applied in teaching practice. This model is proposed with the intention of supporting educators who are seeking to introduce Responsible Design Thinking into their teaching practice, as well as provoking discussion about the current and future state of Design Thinking education.